Fenomena Perilaku Bullying Sebagai Bentuk Kenakalan Remaja - Daffa Rizky Febriansyah; Yuyun Yuningsih (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2024)
This research entitled "Phenonema of Bullying Behavior as a Form of Juvenile Delinquency in SMK TI Pembangunan Cimahi" has the aim to explain how the experience and knowledge of the phenomenon of bullying behavior at school experienced by students who are victims of bullying and the point of view of the Counseling Guidance Teacher and the Vice Principal about bullying behavior that exists in the school environment. The method used in this research is a qualitative method with a phenomenological approach. In the selection of informants using purposive sampling technique and techniques in data collection, namely by conducting observations, in-depth interviews, and documentation of the results of research taken at SMK TI Pembangunan Cimahi. The results of this study suggest categories of bullying behavior that occurs at school such as: physical bullying, verbal bullying, cyberbullying and there are factors that cause bullying behavior such as: individual factors, social interaction factors, and family factors.